Проблемот на вреднувањето во македонскиот политички плурализам или за проблемот на политичкиот плурализам и неговото аксиолошко вреднување - Донев, Дејан (Conrad-Adenauer-Stiftung, 2008)
If there is something that pluralism carries with him in his setting after the system changes, is the process of questioning the previous valid-normed values and offering of new ones. Together with the offer of new values there is a process of opening the field of conflict of interests from the exponents of the political pluralism, as well as the question of valuable system that they are trying to offer us. More precise, the political pluralism opens the question of ethical responsibility and the ability for choosing values which will be incorporate in the conception for further society development. According to the previous, the main imposed question is: does the political pluralism, value by it self, is in condition to build a proper ethical value system through which a certain political phenomenon will be (preventive) evaluated and does this kind of evaluation and taking of certain action if particular political phenomenon is not in accordance with the momentary tendency of society, means reviving to the previous methods of systems for which the most of the people said laud and clear that they are unacceptable. In this context we can also place the question of taking over values from another models of democratic practice and economy and their critical or uncritical implantation-imposting in our settlement. This is the fundamental subject of interest and thinking of the previous imposed thesis.
The problem of evaluation in Мacedonian political pluralism
Keywords: плурализам, аксиологија, политичка етика, вредност